ChemInform Abstract: 1, 8‐Naphthyridine Derivatives: A Review of Multiple Biological Activities. Issue 6 (21st January 2016) - Madaan, Alka; Verma, Ritu; Kumar, Vivek; Singh, Anu T.; Jain, Swatantra K.; Jaggi, Manu
Abstract: Review: 199 refs.